Attendance Management Based on MVC and Laravel in the Municipal Government of Pekanbaru - Sabna, Eka; Yasriady, Dedy; Giatman, M (Jurnal Pendidikan Teknologi Kejuruan, 2021)
Currently, the management of employee attendance in the City Government is still done manually, where the leadership does not have any media that can be used to monitor attendance, causing problems including recapitulation and slow employee attendance reporting. The calculation of the percentage (%) of the employee performance allowance (Tukin) is not carried out proportionally according to the attendance discipline. The impact of the current system is undisciplined employee attendance. Attendance management system which aims to manage employee attendance data. Attendance data obtained every morning and evening is stored on a server at the Pekanbaru City Information and Communication Office. This data is then processed to determine the whereabouts of an employee and become a reference for determining the percentage (%) of the performance allowance that will be received. In addition, this attendance management can be used by Regional Leaders and Heads of Services / Institutions to monitor employee attendance quickly and quickly. The research method used for data collection is to use interviews and literature. While the method in software development uses the method of The Rapid Application Development (RAD). Attendance Management is built on the basis of the Laravel framework using the MVC (Model View Controller) method. The MVC programming pattern that separates logic and views makes program code cleaner, easier to trace when troubleshooting or debugging. The Blade feature of laravel makes using html / php templates simple. This application provides online information about employee attendance. Regional Leaders, Heads of Services / Institutions can monitor the condition of employee absenteeism in Pekanbaru City Government online every day. Employee attendance reports for each Department / OPD are generated automatically. The Personnel and Human Resources Development Agency can use it as a monthly attendance summary report.